Searching the vision of the hummingbird. The expansion of the role of women in ashaninka chamanism - Rojas Zolezzi, Enrique (2022)
Until recently Amazonian chamanism has been described in the ethnographic bibliography as limited to masculine gender, because taboos regarding a biological factor like menstruation blood were considered a restriction to the practice of this function by women. Ashaninka chamanism is involved not only in the preservation of person’s health, but also in that of the natural resources used by these hunter-gatherers. Nowadays however they are confronted with a gradual disappearance of masculine chamanism, because of religious and political persecution and scarcity of resources as a result of settlement in small villages, destruction of forests by the lumber industry and colonization, cattle raising, and pollution of water courses by the activities of drug barons. By these circumstances, taboos are removed, changes are made in the ritual, and a new feminine chamanism arises, so that the traditional system may still reproduce